Knowledge, Compliance and Attitude of Nursing Students towards Standard Precautions: A Cross-Sectional Study in a Tertiary Hospital - Noor Hanita, Z; Nazurah, Z; Khatijah Lim, Abdullah *; Sharifah Shafinaz, S.A.; Yahaya, N. (Faculty of Medicine and Health Sciences, 2023)
Introduction: Knowledge, compliance, and attitudes toward the standard precaution guidelines are crucial to avoid contamination not only on patients but also on healthcare providers. Little is known regarding Malaysian nursing students’ knowledge, compliance, and attitudes toward standard precaution guidelines. The purpose of this study was to look into Malaysian nursing students’ knowledge, compliance, and attitudes towards standard precaution guidelines. Methods: This cross-sectional study was conducted among 337 Diploma nursing students who were chosen by simple random sampling. A self-invented questionnaire based on the CDC recommendations was administered to the participants and their responses were recorded. With a Cronbach’s alpha coefficient of 0.96, the instrument is reliable. The STROBE cross-sectional design process guideline was used as the study design. Results: Majority of the nursing students have adequate knowledge (n=222, 65.9%), adequate compliance (n=229, 68%) and good attitudes (n=171, 50.7%) with the standard precaution. The findings suggest an association between gender (p=0.005) and year of educational level (p=0.001) with the level of knowledge. There was also an association between the level of knowledge with the level of compliance (p=0.029) and the level of attitude (p=0.002) with standard precautions among the nursing students. Conclusion: Even though nearly two-thirds of the participants appeared to have adequate knowledge and compliance, only half of them have good attitudes with the standard precautions. This study indicates that although the students had adequate knowledge and compliance, measures are needed to foster compatible attitudes towards the standard precautions among the nursing students